Analysis of Sociology Textbook for Grade XI: Srikandi Empat Curriculum 2013 Revision - Hardiansyah, Muhammad Agus (Universitas Tanjungpura, 2024)
This research aims to analyze the Sociology textbook for Grade XI, Curriculum 2013 Revised Edition, published by Srikandi Empat. The analysis covers aspects such as content, content presentation, language aspects, and graphical aspects of the book. The results of this analysis meet the criteria set by Minister of Education and Culture Regulation Number 8 of 2016. However, there are still some shortcomings in the book cover, back cover, spine, title page, and language aspects. Nevertheless, in terms of content and content presentation, it complies with the regulations in force and does not affect the content of the book. This research adopts a qualitative approach with content analysis method. The analysis is conducted with reference to Minister of Education and Culture Regulation Number 8 of 2016, including the book cover, introduction, content, conclusion, and student activity content. As a recommendation, the author suggests improving the illustration images to make them more colorful and visually appealing.